A review of published reports regarding zoonotic pathogen infection in veterinarians - Whitney Baker; Gregory C. Gray (2009)
Abstract Objective —To identify published reports regarding zoonotic pathogen infection among veterinarians. Design —Literature review. Procedures —The PubMed electronic database of medical literature published between 1966 and November 2007 was searched. Clinical case reports and reports of outbreak investigations were also identified through searches of the literature outside of PubMed and searches of references listed in included articles. Reports eligible for inclusion included controlled and uncontrolled studies examining seroprevalence of animal pathogens in veterinarians, serosurveys involving veterinarians, and reports of zoonotic pathogen infections causing clinical illness. Results —66 relevant articles were identified. This included 44 seroepidemiologic studies (some examined > 1 pathogen), 12 case reports, 3 outbreak investigations, and 7 self-reported surveys (including 4 related to personal protective equipment use). Of the 44 seroepidemiologic studies, 37 (84%) identified an increased risk of zoonotic pathogen infection among veterinarians, and 7 (16%) identified no increased risk or a decreased risk. Surveys also documented that veterinarians often failed to use recommended personal protective equipment. Conclusions and Clinical Relevance —Our review indicated that veterinarians had an increased risk of infection with a number of zoonotic pathogens. It also suggested that veterinarians may inadvertently serve as biological sentinels for emerging pathogens and could potentially spread zoonotic pathogens to their families, community members, and the animals for which they provide care. Professional and policy measures should be implemented to reduce the risk that veterinarians will become infected with, or transmit, zoonotic pathogens.